University stakeholders’ roles in sustainability integration: challenges and administrative implications for sustainable development - Yassim, Kathija; Adamu, Chidubem Deborah; Uleanya, Chinaza (Frontiers in Sustainability, 2025)
Stakeholder theory emphasizes engaging all stakeholders in sustainability initiatives, while the Triple Bottom Line (TBL) theory balances social, economic, and environmental factors. In Higher Education Institutions (HEIs), both theories address the integration of sustainability. This study assessed stakeholder roles and challenges in HEIs to enhance sustainable growth strategies. A qualitative design with semi-structured interviews in the interpretivism paradigm explored the perspectives of six University of Johannesburg (UJ) stakeholders (students, lecturers, and administrative personnel) who completed an eight-week online Sustainable Development Goals (SDGs) Short Learning Programme (SLP) offered by the institution. Data saturation ensured comprehensive insights without redundancy. Validity was strengthened through triangulation, peer debriefing, member checking, and transparent processes. Ethical approval was obtained. Thematic analysis identified key patterns. Findings suggest that HEIs should prioritize awareness, collaboration, curriculum integration, and long-term strategic programs. Recommendations include funded sustainability approaches, integrating sustainability into curricula, communication plans, specialized committees, professional development, external partnerships, and monitoring frameworks.